Correlation Between Serum Ferritin Levels and COVID-19 Severity: A Retrospective Cross-Sectional Study - Zeynab Marzhoseyni; Zahra Shaghaghi; Maryam Alvandi; Seyyed Hamid Hashemi; Mohammadreza Ghasemi basir; Tieyb Mohamadi; Soghra Farzipour (Journal of Mazandaran University of Medical Sciences)
Background and purpose: The levels of serum ferritin increase with increasing disease severity, thereby suggesting a possible biomarker for the prediction of the cytokine storm. This study was carried out to evaluate the practical utility of ferritin as a serum biomarker in COVID-19. Materials and methods: In this retrospective study, a total of 117 adult hospitalized patients with COVID-19 infection were included. The disease was diagnosed based on clinical signs and chest radiography, followed by real-time PCR. Patients were classified into mild-to-moderate (n= 47), severe (n = 46), and critical (n = 24) groups. Demographic and clinical information, as well as laboratory findings, were collected, and the concentrations of ferritin were compared among the different groups. Results: The highest percentage of patients were in the critical group (76/29%). Overall, COVID-19 infection was more prevalent in females (66%) and the median age of patients in the critical group (76.29) was more than the other ones. The amount of ferritin was significantly higher in the critical (p< 0.001) group. The level of ferritin remarkably was higher in dead patients (620.88 ng/mL. Based on logistic regression analysis and ROC curve, ferritin can be a biomarker to predict high-risk patients. Furthermore, binary logistic regression showed ferritin to be a predictor of mortality supplemented. Conclusion: Serum ferritin is a promising biomarker for anticipating cytokine storm, which may support clinical decision-making and contribute to the optimal management of patients with COVID-19.